Mechanism of the Immune Response to Human Factor VIII in Murine Hemophilia A - Wu, Huiyun; Reding, Mark; Qian, Jiahua; Okita, David K.; Parker, Ernie; Lollar, Pete; Hoyer, Leon W.; Conti-Fine, Bianca M. (Thrombosis and Haemostasis, 2001)
Mice genetically deficient in factor VIII (fVIII) are a model of hemophilia A. As a first step to reproduce in this mouse model what occurs over time in hemophilia A patients treated with human fVIII (hfVIII), we have investigated the time course and the characteristics of their immune response to hfVIII, after multiple intravenous injections. Anti-hfVIII antibodies appeared after four to five injections. They were IgG1 and to a lesser extent IgG2, indicating that they were induced by both Th2 and Th1 cells. Inhibitors appeared after six injections. CD4+ enriched splenocytes from hfVIII-treated mice proliferated in response to fVIII and secreted IL-10: in a few mice they secreted also IFN-γ and in one mouse IL-4, but never IL-2. A hfVIII-specific T cell line derived from hfVIII-treated mice secreted both IL-4 and IFN-γ, suggesting that it included both Th1 and Th2 cells. CD4+ enriched splenocytes of hfVIII-treated mice recognized all hfVIII domains. Thus, hemophilic mice develop an immune response to hfVIII administered intravenously similar to that of hemophilia A patients. Their anti-hfVIII antibodies can be inhibitors and belong to IgG subclasses homologous to those of inhibitors in hemophilic patients; their anti-hfVIII CD4+ cells recognize a complex repertoire and both Th1 and Th2 cytokines, and especially IL-10, may drive the antibody synthesis.Abbreviations used: antibodies, Ab; antigen presenting cells, APC; Arbitrary Units, AU; enzyme-linked immunosorbant assay, ELISA; factor VIII, fVIII; human factor VIII, hf VIII; intravenous, i.v.; optical density, OD; polymerase chain reaction, PCR; phosphate buffered saline solution, PBS; PBS containing 3% bovine serum albumin, PBS/BSA; PBS containing 0.05% polyoxyethylene sorbitan monolaurate, PBS/Tween-20; phytohemoagglutinin, PHA; stimulation index, SI
Keywords: Factor VIII; inhibitors; T cells; immune response